Pengaruh Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa - Vera Octavia; Rahma Rina Wijayanti; Oryza Ardhiarisca; Dessy Putri Andini; Rediyanto Putra (Jurnal Akuntansi Terapan dan Bisnis, 2023)
The purpose of this research is to examine the impact of the use of information technology on the accountability of managing village funds in villages in Pakuniran District, Probolinggo Regency. This study used quantitative methods with research instruments through questionnaires and data analysis techniques in the form of multiple linear regression analysis. The results of this study indicate that the use of information technology have a significant effect on the accountability of managing village funds.